The specifics of the satirical language in kazakh linguistics on the example of gumarakhmetchin’s stories - Akhmetchina, G.G.; Kudritskaya, M.I.; Saden, N.Zh. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
The article determines the features of the Kazakh literary satirical texts on the example of the short stories by Gumar Akhmetchin with the further intention to translate a story by Gumar Akhmetchin «Needle with a broken eye» into English basing on the study of the used linguistic elements.
Keywords: expressive means; satire; parekheza; literary work; translation; trilingualism; stylistics